4 - Influence of Socioeconomic Activities on House Form and Settlement Patterns Among the Tiv People of Central Nigeria - Terna, Aule Thomas; Roshida Binti Abdul Majid,; Mahmud Bin Mohd Jusan, (Africa Development, 2024)
The formation of housing and settlement patterns, such as shape, space enclosure and organisation, are influenced by physical, social and economic factors. However, Rapaport found that sociocultural factors are the primary determinants of built form. This view has been challenged, justifying a replication of the study in other built environments. This study explores the influence of the socioeconomic occupation of the Tiv people in Nigeria on their housing and settlement patterns. The means-end chain qualitative enquiry was applied during interviews with twenty-four participants to determine the inherent socioeconomic values connecting their occupation to settlement pattern. Their settlements were found to be dispersed, with aggregated joint compounds, creating sufficient space for farming. However, the pattern of dispersion of settlements poses security risks. Therefore, transformative efforts are required to aggregate the settlements to make more land available for mechanised agriculture and to enhance people’s safety. More studies are required to reveal the sociocultural values of Nigerian Indigenous housing for sustainable development of their built environments and way of life.